Tartib Al-Qaamus Al-Muhiith Ala Thoriiqah al-Misbaagh Al Munir Wa Asas Al Balaghah - AHMAD Al-ZAAWY, Ath-Thaahir (Riyad: Daar Alam Al-Kutub, 1996)
Tartib Al-Qaamus Al-Muhiith Ala Thoriiqah al-Mirbaagh